Biologia de Gubernetes yetapa (Vieillot, 1818) com ênfase na interação com ambientes úmidos - Wagener, Thuani Luísa Saldanha (2019)
Gubernetes yetapa (Vieillot, 1818) is a bird of the Tyrannidae family (subfamily Fluvicolinae) which is associated with wetlands. These environments, considered one of the most biologically productive on the planet, were historically drained and converted into agricultural crops. Consequently these changes have been harming species which depend on this habitat to live or complete their life cycle. Streamer-tailed Tyrant are known to use these environments for nesting, however little is known about their behavioral ecology and breeding biology, requiring further studies on their natural history and the dynamics with these environments. Thus, the present study aimed to: (1) relate the wetlands importance to the breeding biology of the species; (2) describe breeding aspects of G. yetapa; (3) identify and describe how species interact with the environment and other bird species. The research was carried out in Palmeira das Missões, Rio Grande do Sul state, from November 2017 to January 2019. There were carried out 63 expeditions, biweekly, for each study area, covering the entire photoperiod. During the reproductive period the samples were intensified every three to four days, totalizing a sampling effort of 267.25 h. Animal Focal and Ad libitum methods were used. The conducts performed were grouped into the following categories: Alert, Feeding, Displacement, Maintenance, Reproduction, Social Agonistic, Social NonAgonistic and Vocalization.The species was recorded during all months of sampling, using the wetlands and the surrounding areas. During the reproductive period (October to January) the species showed a preference to perform their behaviors inside the wetlands, while in the nonreproductive period (February to September) it traveled longdistances, being absent from the study areas. In November 2018 a nest containing three eggs were found and were watched by the couple and a third individual, characterized as a nest helper. Three individuals took turns caring for the chicks. G. yetapa presented mixed flock formation in all non-reproductive months, mainly associated with Xanthopsar flavus (f=58.82%; n=70) and Pseudoleistes guirahuro (f=35.29%; n = 42). In the reproductive months, the species chose to conduct its behavior intraspecifically. The most frequent behaviors were alert and feeding. The peak activity of the species occurred between two and three hours after dawn and before nightfall. Streamer-tailed Tyrant have a conservationist interest, because part of their life cycle is closely linked to wetlands, environments which need more attention and studies related to their population dynamics. To know these interactions is fundamental for future studies of conservation of the species and also the environment it occupied.